EFISIENSI PENURUNAN KEKERUHAN, ZAT ORGANIK DAN AMONIAK DENGAN TEKNOLOGI BIOFILTRASI DAN ULTRAFILTRASI DALAM PENGOLAHAN AIR MINUM (STUDI KASUS: PENGOLAHAN AIR BAKU AIR MINUM PDAM PULO GADUNG) - Nurandani Hardyanti; Sudarno utomo; Fikroh Amali (KEAIRAN, 2006)
Ammonia concentration in raw drinking water at Jakarta varied until 2,0 mg/l, that value has reached out the standard of ammonia (1,5mg/l) according to KepMenkes No 907/MENKES/SK/VII/2002. Ammonia in raw water could react with chlor to be choramine, which have lower disinfecting power. It could make chlor consumption being bigger, beside that presence of THMs and chlorophenol as by product of disinfecting is bigger. This research had done in PDAM Pulo Gadung  from December 2004/ January 2005. The purpose of this research was to know effectively of turbidity, organic matter and ammonia removal in raw drinking water by submerged biofilter using honeycomb tube plastic media and ultrafiltration with hollow fiber membrane processes. The feed water entered into the reactor continuously on aerobic and nonaerobic condition with the varied hydraulic residence time from 5-2 hour then continued with ultrafiltration process. Efficiency of ammonia decreased in nonaerobic condition in bioreactor average between from 41,45 - 70,30% and efficiency in ultrafiltration 34,48 - 38,71%. While in aerobic condition in bioreactor average between 44,04-75,00% and in ultrafiltration 35,00 - 38,89%.